Analyzing criminal facility location of illegal airstrips in the Amazon - Lima, Pedro Reis (2025)
Throughout 2021 and 2022, environmental and national defense reports identified over 1,200 illegal airstrips in the Brazilian Amazon - surpassing the number of legalized airstrips in the region. This study investigates the spatial decision making of transnational criminal organizations when selecting locations for these runways in the Brazilian legal Amazon by means of a microeconometric approach. Using precisely georeferenced spatial data provided by the Centro Gestor e Operacional do Sistema de Proteço da Amazônia - CENSIPAM/Ministry of Defense, the entire Amazon area was discretized and runway occurrences were modeled using discrete counting models such as Poisson and Negative Binomial, as well as zero-inflated and hurdle models to account for excess zeros due to the vastness of the study area. The analysis is grounded in economic location theory such as facility location and residential choice modeling; as well classical criminology theories such as rational choice, routine activity, and crime pattern theories to reflect the strategic nature of illegal airstrip placements as key infrastructure to support the flow of criminal procedures; mainly drugs, illegal gold, and timber. Our results highlight the economic rationality with which these organizations have operated in recent years, suggesting that they strategically position airstrips at optimal distances to minimize detection risk while ensuring access to critical public infrastructure, including roads, waterways, ports and legitimate airports.